Dziewiętnastowieczny spór o kodeks Liwiusza z kościoła św. Piotra i św. Pawła w Legnicy - Broda, Michał (Księgarnia Akademicka Publishing, 2024)
NINETEENTH-CENTURY DISPUTE OVER LIVY’S CODEX FROM THE ST. PETER AND ST. PAUL’S CHURCH IN LEGNICA This publication presents a dispute over the codex of Livy from the library of the Church of St. Peter and St. Paul in Legnica, which took place in 1870-1871 between the historian Hermann Kraffert and the philologist Rudolf Peiper in the Silesian newspapers Liegnitzer Stadtblatt, Breslauer Zeitung and Schlesische Zeitung, as well as in the scholarly magazine Jahrbücher für Classische Philologie. It was initiated by a note in Liegnitzer Stadtblatt of 10 May reporting the discovery of a manuscript containing unknown books of Livy’s Ab urbe condita. Several threads are noticeable in the dispute. The first is the question of whether Kraffert was indeed the discoverer of the codex, to which he laid claim; among the others are its age, its value to science, its provenance and its owners, as well as the matter of publicising the discovery worldwide. The dispute also provided an opportunity to present other issues relating to the codex of Legnica and Livy’s manuscript tradition, particularly the fourth decade of the codex, books 31-40. Initially it proceeded in a calm atmosphere, but as time passed, the antagonism between the two adversaries began to grow.